HUBUNGAN LEMBAH SADENG, CEKUNGAN BATURETNO DAN TERAS BENGAWAN SOLO,JAWA BAGIAN TENGAH - Surono Martosuwito; Hanang Samodra; Sidarto Sidarto (Jurnal Geologi dan Sumberdaya Mineral, 2013)
Sadeng valley or ancient river of Sadeng had head water at surrounding Giriwoyo, Wonogiri. Baturetno basin spread outs widely at the south of Wonogiri. When the Old Lawu Mountain erupted, the volcanic products flowed and blocked the Solo River caused big flooding that covered the Baturetno basin. At any time the river might cut the volcanic block, big flooding happed in the valley of the Solo River. As the result, floras and faunas which lived in the valley were got dead. In the next flooding their skeleton were transported and deposited at the Solo terrace. Such things were happened many times. Animal fossils and homonids could possibly much more abundance in the older terraces rather than in the younger one.Key words: Sadeng Valley, Beturetno Basin, Bengawan Solo Terraces, relationship